Sekilas Tentang Manajemen Pajak - Setiawan, Justina Maria (Jurnal Administrasi Bisnis, 2008)
Every tax payer, either personal or organization, where ever there are, they have an obligation to pay taxes. The obligation is written within the law and have to obey by all the tax payer without any exemption. Almost all tax payer tend to avoid the taxes responsibility. This should be acted wisely hence prevented from all taxâs penalty. Using a good tax management, tax payer can do a tax saving without any infringe of the law regulation. The aim of this article is to introduce a basic concept of tax management in order to fulfill the right and obligation in taxes. Tax management will effective if it was arranged according the tax planning which are followed the tax regulation (tax avoidance) and without any tax evasion. The organized tax management should get a back up from the management, carry on ledger and appropriate tax administrative. Keywords: Tax management, tax avoidance, tax evasion